2016
DOI: 10.7585/kjps.2016.20.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Japanese Pine Sawyer, Monochamus alternatus (Coleoptera: Cerambycidae) using Korean Entomopathogenic Nematode Isolates

Abstract: Japanese pine sawyer (JPS), Monochamus alternatus is a vector insect of pine wood nematode, Bersaphlenchus xylophilus in Korea and Japanese pine forest. This study was to evaluate the possibility of biological control of JPS with Korean entomopathogenic nematodes (EPNs). Korean EPNs (Heterorhabditis sp. Gyeongsan, Steinernema carpocapsae GSN1, S. glaseri Dongrae and S. longicaudum Nonsan strain) were infested bate insect, Galleria mellonella in log of dead pine tree. Result showed that, S. carpocapsae GSN1 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…EPNs show greater potential for suppressing Monochamus spp. A study in Korea found that Steinernema carpocapsae (strain GSN1) was able to infect M. alternatus at a depth of 7.5 cm in pine logs (Yu et al, 2016). However, the search for EPNs needs to be widened and research undertaken to ensure that they are compatible with other control strategies (Sousa et al, 2015).…”
Section: Managing the Disease: New Approachesmentioning
confidence: 99%
“…EPNs show greater potential for suppressing Monochamus spp. A study in Korea found that Steinernema carpocapsae (strain GSN1) was able to infect M. alternatus at a depth of 7.5 cm in pine logs (Yu et al, 2016). However, the search for EPNs needs to be widened and research undertaken to ensure that they are compatible with other control strategies (Sousa et al, 2015).…”
Section: Managing the Disease: New Approachesmentioning
confidence: 99%
“…For the control of PWD, physical, chemical and biological methods are generally used, such as felling, fumigation, crushing and burning of pine trees suffering from PWD ( Cai and Lang, 2011 ); reducing the planting quantity of pine forests around the epidemic area; and implementing preventive methods, including injecting chemically synthetic pesticides (emamectin benzoate) ( Ryss et al., 2011 ) into the trunk or spraying insecticides (thiacloprid) into the affected area ( Shin, 2008 ; Yu et al., 2016 ; Zhao et al., 1998 ). However, burning has the potential to cause uncontrollable forest fires that endanger healthy trees and the use of nematicidal chemicals may have adverse effects on forest ecosystems ( Siemann et al., 2008 ; Yi et al., 2015 ) as well as human health ( Kearn et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Post-treatment methods such as felling, fumigation, crushing, and incineration to remove eggs and the larvae of the nematode in infected pine trees are also employed, as well as preventive methods including injection or spraying of pesticides, such as abamectin, into the tree where infection occurs. 19,20 However, because these chemicals are nematicidal, the possibility of adverse effects on the forest ecosystem has been raised. 21,22 In this light, there is an increasing need for low-cost and environmentally friendly alternative control agents.…”
Section: Introductionmentioning
confidence: 99%